Camphor–Thujone Chemotype and Bioactivities of Artemisia herba-alba Asso Essential Oil from Zintan, Libya: Chemical Composition, Antibacterial, and Antiproliferative Effects - Abdulhamid Giweli,; Mona Kremid,; Iman Daw,; Hanen Najjaa,; Rim Gatran,; Abdelkarim Ben Arfa,; Abdulwhab Kammon, (AlQalam Journal of Medical and Applied Sciences, 2025)
Artemisia herba-alba Asso is a medicinal plant renowned for its therapeutic essential oil. This study characterized the chemical profile and bioactivities of the essential oil from Libyan A. herba-alba. The essential oil, obtained via hydrodistillation with a 2% yield, was analyzed by GC-MS/FID and evaluated for antibacterial (disc diffusion) and anticancer (MTT assay) properties. The oil was dominated by camphor (30.53%) and Thujone (22.47%), classifying it as a camphor-thujone chemotype. It exhibited remarkable antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA; 17.33 ± 1.52 mm), and demonstrated potent, dose-dependent cytotoxicity against MCF-7 breast cancer cells with an IC₅₀ of 0.59 mg/mL. The results validate the traditional use of this plant and highlight its potential as a source of antimicrobial and anticancer agents.